Rubric for Assessing ICT Vision, Plan, Policies and Standards in Malaysian Higher Education - Abdul Rahman, Azizah; Alias, Rose Alinda; Mokhtar, Shamsul Anuar (2006)
The paper proposes a rubric for assessing the ICT vision, plan, policies and standards in Malaysian higher education institutions. Based on a selection of twelve survey questionnaires and rubrics that are used to assess ICT implementation, the paper identifies sixteen performance indicators. ICT vision is assessed based on who drives the vision, its focus and the level of awareness and understanding by the campus community. The indicators for ICT plan include the scope of plan, participation in plan development, level of detail, funding for plan and multi-year planning. ICT policies and standards cover the scope, characteristic, participation in the development, level of development and implementation, awareness and understanding by the campus community and how they are reviewed. The paper then uses these indicators to describe the characteristics of three case higher education institutions representing low, moderate and high level of ICT implementation.